Single-cell sequencing reveals reversible glial remodeling in the visual cortex during visual deprivation and recovery - Gong, Xiaoqi; Feng, Jiaojiao; Xu, Zhe; Xie, Yunxiao; Han, Yibo; Li, Jing; Tang, Guodong; Liu, Yuxi; Dong, Xiaoyun; Li, Shuhan; Zhang, Jun; Wang, Junru; et al. (Frontiers in Immunology, 2026)
IntroductionThe visual cortex exhibits remarkable experience-dependent plasticity, which can be profoundly disrupted by abnormal visual input. Form-deprivation myopia (FDM) is a well-established model for studying ocular growth; however, the specific responses and functional roles of non-neuronal cells in the visual cortex during both deprivation and recovery remain poorly understood. This study aimed to comprehensively characterize the dynamic alterations in these cells across the course of deprivation and subsequent visual restoration.MethodsWe employed single-cell RNA sequencing (scRNA-seq) to delineate the transcriptomic landscape of the primary visual cortex (V1) in a guinea pig model. Two-week-old animals were assigned to three groups: normal control (NC), form-deprivation (FDM; 5 weeks of monocular deprivation), and recovery (REC; 4 weeks of deprivation followed by 1 week of restored vision). Key findings were validated using immunofluorescence, quantitative PCR, Western blotting, and transmission electron microscopy. Bioinformatic analyses, including trajectory inference and cell-cell communication mapping, were performed to elucidate cellular dynamics and interactions.ResultsVisual deprivation induced a pronounced pro-inflammatory transformation in microglia compared with the NC group, characterized by significant upregulation of immune-related pathways such as IL-17, TNF-α, and Toll-like receptor signaling. Concurrently, oligodendrocyte numbers were markedly reduced in the FDM group, accompanied by myelin deficits and downregulation of the key transcription factor Zbtb16. Trajectory analysis revealed a blockade in oligodendrocyte differentiation, while intercellular communication analysis indicated enhanced inflammatory signaling from microglia to oligodendrocyte precursors. Notably, the recovery phase largely reversed these alterations: microglial inflammation was substantially attenuated, the expression of myelin-related genes such as Plp1 was restored, oligodendrocyte numbers and myelin integrity were restored to near-control levels, and the differentiation blockade was resolved.ConclusionsThis study demonstrates that non-neuronal cells in the visual cortex, which include microglia and oligodendrocytes, undergo extensive yet reversible reprogramming in response to changes in visual input. These findings highlight a dynamic microglia–oligodendrocyte axis as a critical cellular mechanism underlying cortical plasticity in myopia, suggesting potential molecular targets for visual rehabilitation strategies.